(untitled) (Research, Society and Development, 2021)
The aim of the present study was to evaluate the effect of contact with blood and saline on the change in volume and solubility of calcium silicate cements MTA HP Repair®, Bio-C Repair®, MTA Flow® and Bio-C Repair ION+®. After inserting the materials into retrograde cavities, they were scanned using a microtomograph 1174 (T0), and then placed in contact with blood and saline. After 07 days of contact, the specimens were scanned again (T01), and the volume change and was analyzed. The data were submitted to statistical analysis using the WILCOXON, MAN WHITNEY and KRUSKAL-WALLIS tests (p<0.05). The contact of saline with Bio-C Repair ION+ cement increased its volume. The blood produced an increase in the solubility of MTA HP and MTA Flow. The Bio-C Repair and Bio-C Repair ION+ cements did not undergo change in volume when in contact with blood. Lower volume change values occurred in pre-mixed repair cements when they came into contact with blood.